Pengembangan Usaha Aneka Penganan Tradisional Minang Dalam Meningkatkan Ekonomi Masyarakat - Fera Sriyunianti; Fauna Adibroto; Zulfikar (Akuntansi dan Manajemen, 2021)
There are so many home-based businesses in West Sumatra. One of them is to make traditional cakes typical of the local area. Minang Kabau have many culinary products that have been widely known. Starting small business with household business can be a successful business with many branches. However, not infrequently this business is well developed, and some even stopped. There are many weaknesses in this household business, from production to business management. Some problems are still using simple tool in production process , inefficient and unhygienic production layouts. Another problem is the packaging is simple and simplistic, unattractive the display of products and less professional management. The IbM's goal is to improve the professionalism of home-based cakes through factory lay-out improvements, coconut shell extract packaging, product sales / display counters, PIRTs, trademarks, bookkeeping, management, and product marketing.